Therapeutic Plasma Exchange (TPE) Response in Thrombotic Thrombocytopenic Purpura (TTP): A Case Report - Santoso, Jony; Permana, Septian Adi (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2025)
Background: Thrombotic thrombocytopenic purpura (TTP) is a rare thrombotic microangiopathy. It derives from a severe deficiency of disintegrin-like metalloproteinase with thrombospondin motif type 1 member 13-regulates (ADAMTS13). This case report aims to describe how therapeutic plasma exchange (TPE) with steroids can improve good clinical outcomes in TTP.Case Illustration: A 72-year-old male presented to the emergency department with complaints of fever persisting for 1 week. The patient also complained of a productive cough and shortness of breath. Patient was found apathetic (E3M6V4) and fever (38.1°C). Other vital signs were normal. Thorax examination revealed minimal bilateral basal crackles. Minimal pitting-edema was found in both lower extremities. Patient underwent complete blood count that indicates leukocytosis (shift to the left), thrombocytopenia, hypoalbuminemia, and impaired renal function tests. Chest X-Ray revealed pulmonary edema in both lungs and infiltrates with air-bronchogram in the right paracardiac area. Diagnosis of TTP was established based on history and physical examinations related to TTP pentad criteria (fever, thrombocytopenia, microangiopathic hemolytic anemia, neurological abnormalities, and impaired renal function tests). Patient was then treated with TPE and steroids. Symptomatic treatments for the patient's complaints were given. Patient was then discharged from hospital after treatments.Conclusion: This study provides a review of the expected course of treatment for patients with TTP. Treatment using TPE and steroids can increase platelet counts resulting in significant clinical improvements.